Estimating labour market transitions from labour force surveys: The case of Viet Nam - Brenda Samaniego de la Parra; Christian Viegelahn (International Labour Organization (ILO), 2021)
Labour market transitions that workers experience throughout their working life play an important role in current policy discussions surrounding the future of work. Transitions occur between employment, unemployment and inactivity, but also between formality and informality, as well as between different occupations or industries. This paper discusses methodologies that are available from the literature to estimate the incidence and frequency of transitions using data from labour force surveys, which are run as a rotating panel. The paper then applies these methodologies to Viet Nam in 2011-19, producing estimates of different types of labour market transitions. Without aiming to be comprehensive, this paper provides some examples of what type of data can be produced, demonstrating the feasibility and value of transitions data for labour market analysis.
Keywords: 330; future of work; labour market; labour force; labour statistics; labour force survey